(untitled) (Orchid Insights: A Multidisciplinary Journal of Orchid College, 2026)
This study explores how Nepali private colleges adopt edupreneurial practices. These new approaches are combining responsiveness to the market with their core academic missions. Institutional theory and entrepreneurial orientation offer a framework for examining the interplay between legitimacy and innovation in institutional practices. This provides insight into how competition and survival goals shape the strategic choices. This qualitative study thematically analyzed the collected data through online responses from the institutional leaders (n1 = 5), faculty members (n2 = 5), and senior students (n3 = 7). The key insights highlight that Nepali private colleges mainly adopt edupreneurial strategies in several areas. They focus on strengthening their branding efforts, ensure regulatory compliance, integrate value-added programs and technology. Moreover, they work on expansion of faculty responsibilities, and focusing on career readiness. These strategies are driven not only by commercial success but also by the need for institutions to adapt to a changing environment, sustainability, and social aspects. As a result, edupreneurship emerges as a strategic response to institutional expectations, market pressures, and legitimacy concerns.